2020
DOI: 10.1016/j.ijrobp.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Indoleamine 2,3-Dioxygenase 1 Expression and CD8+ Tumor-Infiltrating Lymphocytes after Neoadjuvant Chemoradiation Therapy and Prognostic Significance in Esophageal Squamous Cell Carcinoma

Abstract: We aimed to evaluate the changes in indoleamine 2,3dioxygenase 1 (IDO1) expression, programmed cell death-ligand 1 expression, and CD8 density after neoadjuvant chemoradiation therapy (CRT) and prognostic significance in 138 patients with esophageal squamous cell carcinoma. Both pre-CRT biopsies and post-CRT surgical specimens were available in 82 patients. IDO1 and programmed cell Purpose: Despite good preclinical evidence, clinical data on the effect of neoadjuvant chemoradiation therapy (CRT) on expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
2
13
0
1
Order By: Relevance
“…In 81 ESCC patients, we did not find a significant association between PD-L1 and 3-year OS and 3-year PFS. Consistent with previous reports [ 18 , 19 ], the expression of PD-L1 was not significantly correlated with patient's prognosis in ESCC patients underwent neoadjuvant treatment and esophagectomy. Differently, Qiao Wang et al [ 15 ] reported that positive PD-L1 was statistically correlated with worse OS ( P = 0.010) in ESCC patients received radical esophagectomy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In 81 ESCC patients, we did not find a significant association between PD-L1 and 3-year OS and 3-year PFS. Consistent with previous reports [ 18 , 19 ], the expression of PD-L1 was not significantly correlated with patient's prognosis in ESCC patients underwent neoadjuvant treatment and esophagectomy. Differently, Qiao Wang et al [ 15 ] reported that positive PD-L1 was statistically correlated with worse OS ( P = 0.010) in ESCC patients received radical esophagectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, some studies have observed that PD-L1 positive ESCC patients have a worse prognosis [ 15 17 ]. Additionally, some studies confirmed that there was no correlation between PD-L1 expression in cancer cells and survival for ESCC patients [ 18 , 19 ]. All the above evidences about the association between PD-L1 in cancer cells and ESCC survival have concentrated on patients with esophagectomy and been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, cold tumors, also known as non-inflamed tumors, are devoid of TILs. Although no study has identified tumor immune categories in EC, it has been reported that a high density of CD8 cells was significantly correlated with more favorable OS and RFS in patients who received post-CRT (18). Similarly, we found that high levels of TILs induced by CCRT were associated with improved clinical response and survival (19).…”
Section: Icis Required For Escc Treatmentsupporting
confidence: 64%
“…В 23 наблюдениях плоскоклеточного рака пищевода не выявлено влияния ХЛТ на плотность CD8+-T-лим фоцитов [16]. Однако в другом исследовании в 82 случаях при плоскоклеточном раке пищевода плотность этих клеток после ХЛТ повышалась [17]. Увеличение плотности CD8+-T-лимфоцитов выявлено и после ХЛТ немелкоклеточного рака легких [18].…”
Section: Discussionunclassified